Provision of Indonesian Preschool Gymnastics to Children to Improve Physical Fitness - tsanyan dary mahdy; dary, tsanyan; irwan, irwan; maihendra anggara, liyant; zidane alfareza, daffa; nuari panggraita, gilang (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2023)
The purpose of the SPI exercise training is to improve physical fitness.The method of implementing this activity was carried out by mutual agreement with the team from SD 2 Karyomukti based on a request from the madrasah. The service for SD 2 Karyomukti children is located in Karyomukti Village, Kesesi District. There are 5 Karyomukti Elementary School 2 students who will take part in the SPI gymnastics service program. This training activity was given 1 meeting. Training is held on Monday at 10.00 WIB until finished. SD 2 Karyomukti field area. The training method used to conduct training is by practicing SPI gymnastics. The output results achieved in this activity are: (1) SD 2 Karyomukti students have better physical fitness. (2) Knowing the science of sports, especially SPI gymnastics besides the religious knowledge studied, has spiritual and physical health.